Indicadores químicos e biológicos de qualidade do solo em sistema de cultivo convencional em Roraima - Dourado, Keila Nunes (2016)
The objective of this research is to evaluate the cultivation system through chemical and biological indicators in the soil in native savanna and transition savanna-forest areas, in the experimental field of Água Boa-Embrapa (CEAB) and Serra da Prata (CESP), Roraima, where two annual harvesting occured (floweing and post-harvest). For the chemical parameters, the pH, Ca, Mg, K, Al, H+Al, P were determined as well as the organic matter of the soil. For the biological, basal respiration, BMS C-, activity of β-glycosidase and acid phosphatase. In the savannah, the pH varied from 5,22 (native vegetation) up to 622 for the corn, the Ca, presented a high content in the cultivation of corn with (1,01 cmolc dm-3) as well as the Mg, with 0, 47 cmolc dm-3 conventional cultivation area 0,03 cmolc dm-3 in native vegetation area. The same was observed for the K and P Al e H+Al with 0,51 cmolc dm-3 e 2,96 cmolc dm-3 respectively. For biological parameters in flowering C-BMS there was a higher concentration in native vegetation with (128,80 mg C kg-1), while the post-harvst, the conventional cultivation of corn showed better result (255,42 mg C kg-1. The basal respiration, in flowering, showed better result in soya (126,26 mg C kg-1). Enzymatic activity of β-glycosidase, in flowering, showed better results in the cultivation of corn with 44.79 μg - nitrosophenol g-1 h-1). However, in the post-harvest there was not a difference between the treatments studied. Acid phosphatase in flowering activity was higher in native vegetation with (531.73 ug - nitrosophenol g-1 h-1 531,73 μg - nitrosophenol g-1 h-1) presented the same result in the post-harvest. In the transition (savannah-forest), the pH varied from 5,45 (corn) to 5,81 (native vegetation). The Ca showed lower content in the soya crop with 1,23 cmolc dm-3. The Mg varied from 0, 23 cmolc dm-3 in conventional crop areas for 0,097 cmolc dm-3 in native vegetation. K and P showed a higher concentration in crop areas,but on the other hand, Al e H+Al showed higher concentration in native vegetation area with 0,13 cmolc dm-3 e 3,18 cmolc dm-3 respectively. For biological parameters in flowering C-BMS had higher concentration in native vegetation with 290.14 mg C kg-1. In the post-harvest, the conventional cultivation of soja showed an increase (285,83 mg C kg-1), coming close to the native vegetation (305,49 mg C kg-1). Basal respiration showed better results in the native vegetation area, in floweing as well post-harvest 153,37mg C kg-1 and 181,66 mg C kg-1 respectively. Enzimatic activity of β-glycosidase in flowering native vegetation was higher in native vegetation (99,39 μg - nitrosophenol g-1 h-1). However, in the post-harvest, a decline was observed by approximately 50%. Acid phosphatase in flowering activity was also higher in native vegetation with (895,34 μg - nitrosophenol g-1 h-1), maintaining the same result as in the post-harvest. Therefore, it was concluded that applying limestone promotes the increased saturation of the cation exchange capacity in the soil and decreases the solubility of some ions in high concentration, which are toxic to crop plants. Biological indicators of soil quality quickly reacted to anthropogenic changes that occur during the replacement of native vegetation for cropping system.